Lunar Rickshaw – A non-Motorized Vehicle Designed for Exploration and Rescue Missions on the Moon’s South Pole - Marius POP; Dan NETOIU; Tiberiu SALAORU; Dana LEPADATU; Calin COMAN; Mircea BOCIOAGA (INCAS Bulletin)
We have designed a simple, lightweight vehicle concept—a Lunar Rickshaw (LR)—engineered to rapidly and safely transport an incapacitated astronaut from a remote location to the Lunar Module (LM). In addition to its primary function for emergency evacuation, the Lunar Rickshaw can also serve as a mobile platform for carrying essential tools during extravehicular activities (EVAs). Key features include a rapid fold/unfold mechanism for quick deployment and stowage, a lightweight design that ensures ease of handling even in bulky spacesuits, and robust encapsulation to prevent lunar dust from affecting moving parts. Additionally, the design incorporates redundant fixing components so that if one fails, another seamlessly assumes the load, ensuring continuous, reliable operation in the harsh lunar environment. Another key aspect of the design is its widened wheel track, which enhances safety, balance, and stability during operation. Additionally, the pulling shaft is initially stored in a folded position for compact stowage. When deployed, it is unfolded and securely locked to the frame using a Lock-and-Walk Mechanism (LWM), ensuring structural rigidity, integrity, and efficient load distribution.